PEMBERDAYAAN KELOMPOK MAJELIS TA’LIM DALAM UPAYA PENCEGAHAN PENYEBARAN COVID-19 DI DESA CINTA KABUPATEN GARUT - Ariani Fatmawati; Sitti Syabariyah; Inggriane Puspita Dewi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Covid-19 has become a global pandemic in early 2020. The government has made efforts to prevent, and spread Covid-19 cases with various efforts. This service activity aims to increase the knowledge of the majlis ta'lim congregation about covid-19 and the processing of medicinal plants to maintain immunity during a pandemic. The service method is by providing education about 5M, vaccination and demonstration of processing herbal plants into drinks. As a result of this activity, the majlis ta'lim congregation understood and implemented the 5M health protocol and most of them had followed the vaccination. In addition, the majlis ta'lim congregation has been able to take advantage of herbal plants in the environment around the house to be processed into herbal drinks. Herbal drinks made by the majlis ta'lim congregation, can also be consumed by the local community but can also be produced to improve the economy of the majlis ta'lim congregation.